Moving Toward Personalized Medicine: Treatment-Focused Genetic Testing of Women Newly Diagnosed With Ovarian Cancer. Issue 5 (1st June 2010) - Trainer, Alison H.; Meiser, Bettina; Watts, Kaaren; Mitchell, Gillian; Tucker, Kathy; Friedlander, Michael
Abstract : Objectives: The presence of a germline BRCA mutation defines a genotype-specific group of women whose invasive ovarian cancer is associated with an increasingly well-defined prognostic and chemosensitivity biological profile. To determine the criteria that may be used to select patients for BRCA treatment-focused genetic testing, we performed a systemic literature search of studies that assessed BRCA1 and BRCA2 mutation frequency in women with ovarian cancer unselected for family history. The results are discussed with regard to the added clinical value gained by identifying a germline BRCA mutation at the time of the ovarian cancer diagnosis. Methods: BRCA-related studies were identified in the CD-ROM databases PubMed (including MEDLINE), PsychINFO, and CINAHL and included in the review if they met the following criteria: they ( a ) assessed mutation frequency in women with ovarian cancer who were unselected for family history and ethnicity, ( b ) were published in a peer-review journal, ( c ) between January 1997 and October 2009, and ( d ) in the English language. Results: Studies investigating the prevalence of BRCA1 or BRCA2 mutations in ovarian cancer patients unselected for family history or ethnicity have found a pathological BRCA mutation rate of approximately 3% to 17%. Without a significant family history, specific features that may be used to target treatment-focused BRCA testing in the ovarian cancer setting include young age at onset (<50 years), high-grade serous tumor histology, and specific ethnicity associated with known BRCA founder mutations. Conclusions: We believe that given the growing appreciation of the prognostic significance of BRCA mutations and the differential chemosensitivity shown by these tumors, as well as the potential of novel agents such as poly(ADP-ribose) polymerase inhibitors, the identification of a germline BRCA mutation concurrent with a new diagnosis of ovarian cancer will significantly impact on tailoring personalized ovarian management in the future.